2020
DOI: 10.1536/ihj.20-043
|View full text |Cite
|
Sign up to set email alerts
|

USP16 Regulates the Stability and Function of LDL receptor by Deubiquitination

Abstract: Low-density lipoprotein (LDL) particles are known to be atherogenic agents in coronary artery diseases. They adjust to other electronegative forms and can be the subject for the enhancement of inflammatory events in vessel subendothelial spaces. The LDL uptake is related to the membrane scavenger receptors, including LDL receptor (LDLR). The LDLR expression is closely associated with LDL uptake and occurrence of diseases, such as atherosclerotic cardiovascular diseases. Our findings identified USP16 as a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Nuclear USP16 also deubiquitinates PLK1 for mitotic chromosome alignment and c-Myc in prostate cancer [ 45 , 46 ]. In the cytoplasm, USP16 deubiquitinates calcineurin for T cell maintenance [ 47 ], LDLR for coronary artery function [ 50 ], RPS27a for 40S ribosomal subunit biogenesis and maturation [ 31 ], and Tektin for male fertility [ 51 ]. USP16 also deubiquitinates proteins in oncogenic pathways, for example, IGF2BP3 in gallbladder cancer [ 48 ], whereas Ct-HBx inhibits the expression level of USP16 in hepatocellular carcinoma [ 40 ], revealing the intrinsic link to cancer development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nuclear USP16 also deubiquitinates PLK1 for mitotic chromosome alignment and c-Myc in prostate cancer [ 45 , 46 ]. In the cytoplasm, USP16 deubiquitinates calcineurin for T cell maintenance [ 47 ], LDLR for coronary artery function [ 50 ], RPS27a for 40S ribosomal subunit biogenesis and maturation [ 31 ], and Tektin for male fertility [ 51 ]. USP16 also deubiquitinates proteins in oncogenic pathways, for example, IGF2BP3 in gallbladder cancer [ 48 ], whereas Ct-HBx inhibits the expression level of USP16 in hepatocellular carcinoma [ 40 ], revealing the intrinsic link to cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…LDL is taken up by membrane scavenger receptors, including LDL receptor (LDLR) [ 63 ]. Through screening the siRNA library against the USP family of DUBs, USP16 was found to affect LDL the most [ 50 ] ( Figure 4 J). Subsequent studies revealed that USP16 does not regulate the transcription of LDLR but regulates its protein stability.…”
Section: The Substrates and Functions Of Usp16mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, USP16 is implicated in T-cell mediated immunity [ 65 ], and also in the LDL receptor stability and activity [ 66 ]. The latter function could have relevant implications in the piglets of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitin carboxyl-terminal hydrolase 16 (USP16, also called UBPM), a widely expressed deubiquitinase, has been implicated to function in cell proliferation, division, and differentiation 11 , 12 . It specifically deubiquitinates H2A histones, and thereby regulates gene transcription and DNA repair 13 .…”
Section: Introductionmentioning
confidence: 99%